Array gain and phase calibration in the presence of multipath based on weighted spatial smoothing - WANG Bu-hong1; WANG Yong-liang2; CHEN Hui2 (Tongxin xuebao)
Despite the potential advantages offered by high-resolution direction-of-arrival(DOA)estimation methods, their application to real systems has been very limited. One of the main reasons for this situation is the lack of robustness of these methods to the perturbations in the array manifold. Although the importance of proper array calibration has been recognized widely and many array calibration algorithms have been reported extensively in the literature,the array calibration in the presence of multipath has received relatively little attention. Based on the idea underlying weighted spatial smoothing algorithm for coherent sources DOA estimation, a novel cost function is constructed in this paper to achieve favorable array calibration in the presence of multipath. Simulation results using genetic algorithm are provided to demonstrate the effectiveness and behavior of the proposed algorithm